História da Filosofia - Nicola Abbagnano (Editorial Presença, 1979)
Vol. 2: trad. António Borges Coelho, 2.ª edição, 253 p.; Vol. 3: trad. Armando da Silva Carvalho, 2.ª edição, 287 p.; Vol. 4: trad. José Garcia Abreu, 2.ª edição, 242 p.; Vol. 5: trad. Nuno Valadas, António Ramos Rosa, 2.ª edição, 319 p.; Vol. 6: trad. António Ramos Rosa, 3.ª edição, 1982, 174 p.; Vol. 7: trad. António Ramos Rosa, António Borges Coelho, 3ª edição,1982, 217 p.; Vol. 8: trad. António Ramos Rosa, António Borges Coelho, 2.ª edição, 279 p. ; Vol. 9: trad. António Ramos Rosa, António Borges Coelho, 2.ª edição, 262 p. ; Vol. 10: trad. Armando da Silva Carvalho, António Ramos Rosa, 2.ª edição, 260 p.; Vol. 11: trad. António Ramos Rosa; 2.ª edição, 239 p.; Vol. 12: trad. António Ramos Rosa, Conceição Jardim, Eduardo Lúcio Nogueira; 2.ª edição, 273 p.; Vol. 13: António Ramos Rosa, Conceição Jardim, Eduardo Lúcio Nogueira; 2.ª edição, 274 p.; Vol. 14: trad. Conceição Jardim, Eduardo Lúcio Nogueira, Nuno Valadas; 2.ª edição,353 p.;